2022
DOI: 10.1097/md.0000000000029257
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology explores the mechanisms of Eucommia ulmoides cortex against postmenopausal osteoporosis

Abstract: Postmenopausal osteoporosis (PMOP) has become one of most frequent chronic disease worldwide with aging population. Eucommia ulmoides cortex (EU), a traditional Chinese medicine, has long since been used to treat PMOP. The aim of this study is to explore pharmacological mechanisms of EU against PMOP through using network pharmacology approach.The active ingredients of EU were obtained from Traditional Chinese Medicine System Pharmacology database, and target fishing was performed on these ingredients in UniPro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Moreover, traditional Chinese medicine has a vital role in preventing osteoporosis. Eumoides [403], Epimedium [404], and Liuwei Dihuang pill [405], a classic formula for invigorating kidneys, have been widely used in the treatment of postmenopausal OP for a long time. Qing'e-decoction has also been confirmed to regulate bone metabolism, improve bone quality and delay bone aging, which may be achieved by increasing sex hormones, serum leptin receptor, and leptin receptor [406].…”
Section: Drug Therapymentioning
confidence: 99%
“…Moreover, traditional Chinese medicine has a vital role in preventing osteoporosis. Eumoides [403], Epimedium [404], and Liuwei Dihuang pill [405], a classic formula for invigorating kidneys, have been widely used in the treatment of postmenopausal OP for a long time. Qing'e-decoction has also been confirmed to regulate bone metabolism, improve bone quality and delay bone aging, which may be achieved by increasing sex hormones, serum leptin receptor, and leptin receptor [406].…”
Section: Drug Therapymentioning
confidence: 99%
“…[21,22] With the aid of database information and network construction of "Medicine-Targetspathways-Disease," network pharmacology can effectively predict the potential mechanisms of Chinese herbs in treating various diseases. [23][24][25] In the present study, we investigated the pharmacological mechanisms of Lycii Fructus against PMOP by using network pharmacology. The targets related to Lycii Fructus and PMOP were screened out through several databases.…”
Section: The Study Was Supported By Natural Science Foundation Of Nin...mentioning
confidence: 99%
“…[ 21 , 22 ] With the aid of database information and network construction of “Medicine-Targets-pathways-Disease,” network pharmacology can effectively predict the potential mechanisms of Chinese herbs in treating various diseases. [ 23 25 ]…”
Section: Introductionmentioning
confidence: 99%
“…Eucommia ulmoides , as recorded in ancient books of Chinese medicine, was recommended for the treatment of osteoporosis for a long time [ 9 ]. Previous studies suggested that the anti-osteoporosis effects of E. ulmoides involved in angiogenesis, cell proliferation and inflammatory response via mediating various biological processes [ 10 ]. Aucubin, an iridoid glycoside primarily derived from E. ulmoides , displays potential effect to decelerate the development of osteoporosis through inhibiting osteoclast activity and enhancing bone formation in different osteoporosis models [ 11 ].…”
Section: Introductionmentioning
confidence: 99%